Differences in the quantity and intensity of playing in elite soccer players of different position in the game - Ademovic, A. (Homosporticus, 2016)
The aim of this study was to determine differences in the amount and intensity of movement of top players in terms of the position in the team, on a sample of 167 players who played all 90 minutes of the eighth finals of the World Cup 2010 in South African Republic. By comparing the players` position it was found that the midfield players, on average, most ran, (10952 ± 2123m), which is the case and the amount of movement when the team in possession (4279 ± 1099m) and when the team is not in possession of the ball (4485 ± 1010m). In relation to the intensity of the defensive players during a game on average the most time spent in the low intensity (83.86 ± 2.92%), the activities of medium and high intensity most spent midfielders (10.44 ± 1.47% of total distance traveled). The highest maximum average speed achieved attackers (24.24 ± 3.07 km / h). Canonical discriminant analysis obtained three discriminant functions of which two have statistically significant value (Canonical Cor. = 893, p = .00) and Canonical Cor. = 488; p = .00). The highest correlation with the first isolated discriminant function, which maximally different positions in the team (Wilks Lambda = 143; p = .00), have all three variables that determine the intensities of movement, variables that determine the total length of the distance traveled, distance covered in possession and the amount of players, a dominant position is midfield players. The second isolated discriminant function that also statistically significantly different position in the game (Wilks Lambda = 709; p = .00) variable determines the amount of distance traveled without the ball, but the most dominant group are defenders, then midfielders.